Problem amalgamacji przemysłowej (zjednoczenia i kombinaty) - Skowroński, Antoni (Wydział Prawa i Administracji UAM, 1971)
Having analyzed theoretical models of economic associations the author proceeds to the activities of specialized associations and industrial combines and sets up propositions respecting their future activities. The main reasons for creation of industrial amalgamations are the rapidly changing relations between economic factors influenced by technical progress and the modern organized market. The author declares for the type of association known as part amalgamation whose role would consist in limited control of subordinate enterprises and that would be the actual representative of the enterprises, and not a representative of the ministry only. All the affairs the enterprises are not able to deal with under the conditions of planned economy should fall within the competence of the association, namely, establishement of research centres, approval of plans, organization of supplies for the subordinate enterprises, organization of outlets, and first of all development of technical progress and co-ordination of the represented industrial branch. This would smooth away a lot of difficulties faced by industrial associations, i. e. difficulties concerning production, distribution, location, investments and finances.
The Question of Industrial Amalgamation (Associations and Combines)